AN ANALYSIS OF CODE SWITCHING AND CODE MIXING USED BY GITA SAVITRI IN HER VIDEO ENTITLED “EVERYTHING WRONG WITH HUSTLE CULTURE” - Lilis Nurhasanah (PROJECT (Professional Journal of English Education), 2021)
There are many languages in this world which used as a tool of communication. For that reason many people are bilingual or even multilingual. The ability to speak in more than one language is causing the sociolinguistic phenomenon called code switching. Code switching is the situation when someone switches his language from one into another. This is commonly happening everywhere includes in Indonesia. There are many Indonesian people who have bilingual or multilingual competence who often do code switching. One of them is Gita Savitry, a famous young Youtuber. For that reason this research is trying to find out the code switching that Gita’s used, classify it and explain the reason behind it. Furthermore this is a descriptive qualitative research, and the data was taken from Youtube website. The finding showed that to most dominant type occurring in the speech video was intra sentential switching, it occurred 40 times or 80, 10% of total code switching occurred. Mainly, the reason for using code switching is related to particular topic which is talked. Furthermore the other reasons are lexical needed, interjunction, emphasizing or clarifying statement and showing solidarity. Keywords:  Code Switching, Code Switching Types, Code Switching Reason